2022
DOI: 10.1108/tqm-07-2021-0218
|View full text |Cite
|
Sign up to set email alerts
|

An augmented reality-based system for improving quality of services operations: a study of educational institutes

Abstract: PurposeThis study aims to evaluate the usability of the augmented reality-based Evoke Education System (EES) to improve service operations in educational settings. The EES uses an animated character (Moe) to interact with children in a classroom by reproducing their teacher's movements and speech.Design/methodology/approachThis study uses a quantitative approach for the system usability evaluation. The ESS was evaluated by 71 children aged 6–8 years old, from two primary schools. After interacting with the EES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…The pie chart (see Figure 3) represents the distribution of primary studies that have utilized these technologies. According to the chart, augmented reality is the most used immersive technology in studies aiming to enhance students' learning, with 11 studies ([5], [6], [9], [10], [11], [18], [19], [20], [21], [22], [23]) out of 17 primary studies. Augmented reality taking the lead at 11 studies, indicating its significant role in current educational enhancement and greater adoption in practical applications or its relevance in current educational methodologies.…”
Section: Rq1: What Are the Trends And Impacts Of Immersive Technology...mentioning
confidence: 99%
See 1 more Smart Citation
“…The pie chart (see Figure 3) represents the distribution of primary studies that have utilized these technologies. According to the chart, augmented reality is the most used immersive technology in studies aiming to enhance students' learning, with 11 studies ([5], [6], [9], [10], [11], [18], [19], [20], [21], [22], [23]) out of 17 primary studies. Augmented reality taking the lead at 11 studies, indicating its significant role in current educational enhancement and greater adoption in practical applications or its relevance in current educational methodologies.…”
Section: Rq1: What Are the Trends And Impacts Of Immersive Technology...mentioning
confidence: 99%
“…Meanwhile, due to the disruption caused by the COVID-19 pandemic, schools have had to adapt their curriculum, leading to an increased interest among educators in finding suitable and efficient technologies for online learning [11]. Immersive technology can be utilized in emergency situations where remote learning becomes the only option [9].…”
Section: Introductionmentioning
confidence: 99%
“…The authors further added that the users may experience it on a computer screen or through other devices, such as projectors, digital boards, special glasses, or 3G mobile phones. The ability of AR to enhance reality with computer-generated sights, sounds and data will change how students view and interact with the world (Egaji et al, 2022), whereas previously education relied primarily on teachers to deliver course content in the classrooms. The two most popular formats for utilising AR in learning and teaching processes, according to Billinghurst and Dunser (2012), are augmented books and AR apps for handheld mobile devices.…”
Section: Literature Review Application Of Augmented Reality (Ar) Tech...mentioning
confidence: 99%
“…Recently, the Covid-19 pandemic caused entire campuses and classrooms to switch their attention to online learning using digital media. Digital technologies are used to teach millions of students (Williamson, 2021;Egaji et al, 2022). As specified by Isaías ( 2018), the majority of learning materials will be digitalised in the future, and there will be widespread use of online courses, digital libraries, and global internet access.…”
Section: Impact Of Pandemic Crisis Over the Practicality Of Ar In Edu...mentioning
confidence: 99%
“…They demonstrated that failing to consider such elements means foregoing a comprehensive, effective and accurate research of work dynamics in logistics systems. In the fifth paper, “An augmented reality-based system for improving quality of services operations: a study of educational institutes,” Egaji et al (2022) suggest that AR-based training programs potentially increase their knowledge retention and are essential for improving the quality of service operations.…”
Section: Special Issue Papersmentioning
confidence: 99%